Evaluation of a petit tissue microarray in a tertiary care histopathology laboratory – a prospective study - Dr. Priavadhana Rajan Prasaad; Dr. Srilakshmi Priya V; Dr. Bheema Rao G.; Dr. B.O. Parijatham; Dr. Lakshmi Prabha V (Tropical Journal of Pathology and Microbiology, 2018)
Background: With the advancements in pathology for diagnosis of tumors, there is a need for technologies which provide test results with a short turn-around time. Also, with the increasing incidence of early diagnosis of tumor, detection of prognostic markers becomes a necessity. Tissue Micro-Array is one such technology in which tumor diagnosis, tumor markers and prognostic markers could be studied with limited tissue sample at a low cost. In this study, we evaluated the feasibility of a petit Tissue Microarray for immunohistochemical profiling of breast carcinomas.Materials and Methods: Tissue cores were obtained from random tissues which included placenta, breast tissue and lymphnode and endometrium using skin punch biopsy needle of bore 2 mm. These were done for standardizing the procedure of a miniature tissue microarray. Further, tissue cores obtained from carcinoma breast tissue by two different methods were used for constructing a microarray block. Sections of 4 micron thickness were taken and stained with hematoxylin and eosin stains. If satisfactory tumor tissue is present in this constructed block, then sections were taken for immunohistochemistry staining with ER, PR and HER2.Results: Directly constructed tissue blocks had better preservation of tumor tissue morphology compared to the blocks constructed from donor blocks. Also, directly constructed tissue blocks had the advantage of not mutilating the donor block which could be still used for further studies and reference. Immunohistochemistry revealed similar results as obtained during the routine histopathological sections. Also, the cost of the reagents used for immunohistochemistry was reduced by 200% as compared to the routine immunohistochemical staining procedure.Conclusion: A petit Tissue microarray is definitely possible in a tertiary care histopathology laboratory and can be utilized for immunohistochemical studies with multiple markers.